Nature versus Nurture in Social Mobility under Private and Public Education Systems - Simon Fan; Yu Pang; Pierre Pestieau (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This paper analyzes the roles of innate talent versus family background in shaping intergenerational mobility and social welfare under different education systems. We establish an overlapping-generations model in which the allocation of workforce between a high-paying skilled labor sector and a low-paying unskilled labor sector depends on talent, parental human capital, and educational resources, and the wage rate of skilled workers is governed by their average talent. Our model suggests that under the private education system, income inequality is inversely associated with social mobility, and the steady-state average talent of skilled workers declines as people make greater educational investments on their children. Under the public school system, the allocation of workforce depends more on talent and less on family background. Consequently, both intergenerational mobility and income inequality increase, and social welfare may improve under reasonable conditions. Moreover, if some parents are myopic, public education may yield the highest welfare.
Keywords: H20; H31; H50; O11; 330; innate ability; private education; public education; intergenerational mobility